2022
DOI: 10.3390/ma15196640
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conductivity Stability of Interfacial in Situ Al4C3 Engineered Diamond/Al Composites Subjected to Thermal Cycling

Abstract: The stability of the thermal properties of diamond/Al composites during thermal cycling is crucial to their thermal management applications. In this study, we realize a well-bonded interface in diamond/Al composites by interfacial in situ Al4C3 engineering. As a result, the excellent stability of thermal conductivity in the diamond/Al composites is presented after 200 thermal cycles from 218 to 423 K. The thermal conductivity is decreased by only 2–5%, mainly in the first 50–100 thermal cycles. The reduction o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Therefore, exploring thermal interface materials (TIMs) with high thermal conductivity has become crucial. Ideal TIM materials require good mechanical properties to match the inherent surface roughness and maintain good contact of heater and heat sink during thermal cycling along with excellent heat transfer performance. Polymer-based materials are widely used in TIMs due to their excellent mechanical properties and processability. However, their thermal conductivity is low and unstable at high temperatures, which has led to the development of alternative methods to enhance the performance of the high polymer matrix-based TIMs by adding high thermal conductivity materials, such as metal (Al, Ag, and Cu), ceramic (Al 2 O 3 , BN, and SiC , ), and carbon-based fillers (diamond, carbon fiber, and graphene ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, exploring thermal interface materials (TIMs) with high thermal conductivity has become crucial. Ideal TIM materials require good mechanical properties to match the inherent surface roughness and maintain good contact of heater and heat sink during thermal cycling along with excellent heat transfer performance. Polymer-based materials are widely used in TIMs due to their excellent mechanical properties and processability. However, their thermal conductivity is low and unstable at high temperatures, which has led to the development of alternative methods to enhance the performance of the high polymer matrix-based TIMs by adding high thermal conductivity materials, such as metal (Al, Ag, and Cu), ceramic (Al 2 O 3 , BN, and SiC , ), and carbon-based fillers (diamond, carbon fiber, and graphene ).…”
Section: Introductionmentioning
confidence: 99%
“…7−10 Polymer-based materials are widely used in TIMs due to their excellent mechanical properties and processability. However, their thermal conductivity is low and unstable at high temperatures, which has led to the development of alternative methods to enhance the performance of the high polymer matrix-based TIMs by adding high thermal conductivity materials, such as metal (Al, 11 Ag, 12 and Cu 13 ), ceramic (Al 2 O 3 , 14 BN, 15 and SiC 16,17 ), and carbon-based fillers (diamond, 18 carbon fiber, 19−22 and graphene 23−.25 ). Metal fillers have high thermal conductivity, but their corrosion resistance is weak, and their high density increases the burden of electronic components.…”
Section: Introductionmentioning
confidence: 99%
“…While improving the thermal conductivity of diamond/aluminum composite is considered, the performance stability of the composite cannot be ignored. Few research on the stability of diamond/aluminum composites have been reported [ 22 , 23 , 24 ], regarding the effects of temperature shock and hydrothermal treatment on diamond/aluminum composites. As far as we know, there is no report on the corrosion behavior of diamond/aluminum composites.…”
Section: Introductionmentioning
confidence: 99%